Exit and voice : the paradox of cross-border politics in Mexico - Duquette-Rury, Lauren (University of California Press, 2020)
"Sometimes leaving home allows you to make an impact on it-but at what cost? Exit and Voice is a compelling account of how Mexican migrants with strong ties to their home communities impact the economic and political welfare of the communities they have left behind. In many decentralized democracies like Mexico, migrants have willingly stepped in to supply public goods when local or state government lack the resources or political will to improve the town. Though migrants' cross-border investments often improve citizens' access to essential public goods and create a more responsive local government, their work allows them to unintentionally exert political engagement and power, undermining the influence of those still living in their hometowns. In looking at the paradox of migrants who have left their home to make an impact on it, Exit and Voice sheds light on how migrant transnational engagement refashions the meaning of community, democratic governance, and practices of citizenship in the era of globalization"--